Mental Health care by non-psychiatry physicians - Calderón-Viacava, José Luis (2024)
The main objective of this article is to substantiate the importance of the non-psychiatrist physicians' role in theintegrating process of physical and mental health care as a unit in which both exhibit a reciprocal impact. On the basis of aglobalized context in the understanding of health, conceptual bases of health care are examined from a multidimensionalperspective that incorporates the challenges of wellbeing, identifying the current critical knots whose improvement wouldfacilitate a rout to the integral care postulated by the person-centered medicine. This renewed paradigm requires to startwith detection and diagnosis linking both physical and mental health as a dynamic unit. To reach such purpose,information about mental health and its management within the health services is presented to, finally, suggest a careframe adequate to postulates of the person-centered medicine.